From Transition to Market Evidence and Growth Prospects - Sahay, Ratna (International Monetary Fund, 1998)
This paper presents evidence on the behavior of output and inflation in the transition economies during 1992-95. A regression analysis explores the differences in output performance across the transition economies during this period. The paper then engages in a numerical, somewhat speculative, exercise to assess the long-run growth potential of the transition economies. It concludes that it should take about 20 years for the faster reformers to reach current OECD per capita levels